IMPLIKASI PERUBAHAN NILAI KOMPETENSI INTI, KOMPETENSI KEPEMIMPINAN DAN KOMPETENSI TEKNIS DALAM KINERJA PER INDIVIDU KARYAWAN PT SEMEN TONASA - Andi Ririn Oktaviani (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of this research is to know the cause of fluctuation of core competency value, leadership competence and technical competence per individual employee which impact on performance value per individual employee at PT Semen Tonasa. This research using explanatory pattern (explanatory) is a research that intends to explain the position of the variables studied and the relationship between one variable with other variables. In the explanatory, done in two stages, in the first stage more emphasis on the collection and analysis of quantitative data and then proceed with a qualitative approach to describe or explain further quantitative findings. (Dale in Lodico, Spaulding, & Voegtle, 2006). The results of the general research of each employee has met the target achievement of the three competencies that are expected, but based on the data competence per individual and then classified based on the scale shows that there are still most employees who are in the average or moderate competence (scale 3) and even some individuals which are on a scale of 2 or incompetence and scale 1 or failed.